2019
DOI: 10.16965/ijar.2019.125
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Palatal Indices and Foramina in the Hard Palate of Adult Human Skulls in Central India Region

Abstract: The aim of the study is to determine morphometric indices of hard palate, position and location of greater palatine foramen (GPF) in relation to maxillary molars and number of lesser palatine foramen (LPF).Materials and methods: 100 adult skulls (65 males and 35 females) were obtained from the Department of Anatomy. The parameters of hard palate like length, breadth and height were measured and palatine indices were calculated. Observations were made on the position and relation of GPF with maxillary molar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The percentage of the broad palate (brachystaphyline) was 31% in male skulls and 31% in female skulls, with no significant statistical difference between male and female skulls. Other studies reported similar findings [ 21 , 22 ]. They also opine that around 63% of Indian skulls studied by them had a narrow palate followed by a broad palate.…”
Section: Discussionsupporting
confidence: 84%
“…The percentage of the broad palate (brachystaphyline) was 31% in male skulls and 31% in female skulls, with no significant statistical difference between male and female skulls. Other studies reported similar findings [ 21 , 22 ]. They also opine that around 63% of Indian skulls studied by them had a narrow palate followed by a broad palate.…”
Section: Discussionsupporting
confidence: 84%